An Exploratory Study on Challenges of E-Commerce Adoption in Birendranagar, Surkhet - Dhungana, Dillu Prasad (Journal of Entrepreneurship & Management Studies, 2024)
The past few decades have witnessed a significant transformation and rapid growth of electronic business and trade. E-commerce is flourishing in developed countries, but disparities are emerging among developing nations. This paper provides a concise overview of the state of e-commerce in Birendranagar, Surkhet, based on an extensive literature review and analysis of data. this exploratory study focuses on a population of e-commerce users in the Birendranagar surkhet. Using purposive sampling, a sample of 55 participants provides valuable insights into the specific hurdles faced by both customers and vendors. It examines the current situation and the varying adoption rates of new technologies. Furthermore, the paper discusses the major obstacles hindering the growth and development of e-commerce. Finally, it is recommended that local businesses and policymakers collaborate to address the requirement of e-commerce users like digital literacy, conducive environment and training & development and, targeted efforts towards improving infrastructure.